DENTAL EDUCATION PAKISTAN (DEP) VISION 2025: A WAY FORWARD, TOWARDS PROGRESSION & GLOBALIZATION: Guest Editorial on Dental Education - Katpar, Shahjahan; Almas, Khalid (Pakistan Armed Forces Medical Journal, 2021)
Abrahim Flexner, considered “Father of Modernday Medical Education” about a century ago revolutionized entire Health Education & Service Structure bypublishing his shivering report based on standards, resulted in closure of compromised academic institutes and transformed the entire USA/Canadian Health Sector, including Dentistry. His report strongly demanded, appropriate knowledge and skills application to avoid compromised patient care, as the most important aspect required for ailing humanity and this also includes oral/ dental health care. We feel that the current Dental Education Pakistan (DEP) also needs similarreports to attain excellence & “globalization” to be at par with international standards.